(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Atopic Dermatitis (AD) is a chronic, highly pruritic inflammatory skin disease. The lesions are characterized by papules, papulovesicles, edema, crusting and scaling with hyperpigmentation or hypopigmentation after healing. Here we represent a case of AD, having dry, pruritic and highly lichenificated skin lesion on lateral aspect of left leg from last 4 years. Based upon correlation in sign and symptoms the disease was considered as Vicharchika as per Ayurvedic perspective and treated accordingly with three sitting of wet cupping (bloodletting using vacuum cups) at interval of every 3-months gap on basis of the Samprapti (pathology) of Kushta Vyadhi comprising of all three Dosha Vata, Pitta and Kapha along with Rakta, Lasika, Twak, Mamsa as Dushya. Raktamokshana using wet cupping technique showed good result in reducing the sign and symptoms of eczema upto 90%. Based upon observation it can be concluded that Raktamokshana is found to be effective in management of Atopic Dermatitis.